Plaintext Related Two-level Secret Key Image Encryption Scheme - Yong Zhang; Jiali Xia; Peng Cai; Bin Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Some chaos-based image encryption schemes using plain-images independent secret code streams have weak encryption security and are vulnerable to chosen plaintext and chosen cipher-text attacks. This paper proposed a two-level secret key image encryption scheme, where the first-level secret key is the private symmetric secret key, and the second-level secret key is derived from both the first-level secret key and the plain image by iterating piecewise linear map and Logistic map. Even though the first-level key is identical, the different plain images will produce different second-level secret keys and different secret code streams. The results show that the proposed has high encryption speed, and also can effectively resist the existing cryptanalytic attacks. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1599